Importance of numbers and analysis of cash flows at community colleges self-funded case study in the Faculty of the University of safe - fedaa abdulmajid sabbar; thamer mahdi mohammad (Iraqi Journal for Administrative Sciences, 2024)
The littleness of financial destinations, phiher education and the weakness of university open. End is considered as the main reasons that prevent the participating, of Iraqi universities in getting its scientific goals. The civil colleges of self – open end as one of the substitute which helps the society in continuing the higher education in the suitable way through making pupils of such colleges pay the money of their study. And here we see the importance of the suitable use and suitable dispensation of the available resources such as the payed money in such colleges the process of preparing the monetary cash flaws in such colleges in the right way and financial analysis of such a list is considered as the most important methods which help evaluate the financial process of such colleges in the right way and financial analysis of such a list is considered as the most important methods which help evaluate the financial process of such colleges. This paper aims to show the importance of preparing such list in its right way according to the arrangements of the only one account system in addition to show the importance of making the process of financial analysis of the list itself. The researcher gets a conclusion which is that the workers in the financial affairs section, Al Mammon college, find difficulty in preparing such a list because there is no general sample from the superintendence of the college which help showing the way of preparing such a list though they must do it since (2005 ) also, the college could not do the financial analysis though the importance of such analysis in giving a clear picture for the higher management of the college about the financial resources and way and its use. The researcher recommends giving a general sample of preparing the list shown in the annexation (num1) of this paper in the civil colleges to follow it, and also to do the processes of financial analysis of the list for its importance shown above.